Reversible cytoplasmic localization of the proteasome in quiescent yeast cells - Damien Laporte; Bénédicte Salin; Bertrand Daignan‐Fornier; Isabelle Sagot (2008)
The 26S proteasome is responsible for the controlled proteolysis of a vast number of proteins, including crucial cell cycle regulators. Accordingly, in Saccharomyces cerevisiae, 26S proteasome function is mandatory for cell cycle progression. In budding yeast, the 26S proteasome is assembled in the nucleus, where it is localized throughout the cell cycle. We report that upon cell entry into quiescence, proteasome subunits massively relocalize from the nucleus into motile cytoplasmic structures. We further demonstrate that these structures are proteasome cytoplasmic reservoirs that are rapidly mobilized upon exit from quiescence. Therefore, we have named these previously unknown structures proteasome storage granules (PSGs). Finally, we observe conserved formation and mobilization of these PSGs in the evolutionary distant yeast Schizosaccharomyces pombe. This conservation implies a broad significance for these proteasome reserves.